2020
DOI: 10.1016/j.biombioe.2020.105884
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of cellulose pyrolysis oil by a Clostridial bacterium

Abstract: The coupling of thermochemical and biological conversion of biomass is a promising strategy to produce chemicals in future integrated biorefineries. Indeed, thermochemical conversion such as pyrolysis is a fast process without any solvent or enzyme for the depolymerization of biomass. In this work, cellulose was pyrolyzed to produce sugars which have been then fermented by bacteria (Clostridium acetobutylicum) to produce acetone and butanol. This type of bacteria presents an interesting biological platform: it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…, di or tri-hydroxybenzenes), anhydro-oligosaccharides formed by cellulose ejection, humin-like matter, and hybrid oligomers formed by lignin and cellulose. WS is bioavailable and partially biodegradable, , and selected fractions of WS ( e.g. , AS and VFA) were successfully converted with HTB schemes by several authors. Whole WS can be converted to methane by anaerobic digestion in 55–76% yield, , and healthy microbial consortia can degrade most of the GC–MS detectable portion of WS. …”
Section: Introductionmentioning
confidence: 99%
“…, di or tri-hydroxybenzenes), anhydro-oligosaccharides formed by cellulose ejection, humin-like matter, and hybrid oligomers formed by lignin and cellulose. WS is bioavailable and partially biodegradable, , and selected fractions of WS ( e.g. , AS and VFA) were successfully converted with HTB schemes by several authors. Whole WS can be converted to methane by anaerobic digestion in 55–76% yield, , and healthy microbial consortia can degrade most of the GC–MS detectable portion of WS. …”
Section: Introductionmentioning
confidence: 99%
“…There have been studies that reported performance and kinetics of LGA hydrolysis, the most of which employed homogeneous reaction system with mineral acids or enzymes as the catalyst. [15,16] However, the use of homogeneous catalyst often suffers from problems such as separation of catalyst from the product liquid, the catalyst recyclability, corrosion of reactor materials, and treatment of waste stream. Recently, Abdilla-Santes et al [17] reported that an acidic resin was available as the heterogeneous catalyst for the hydrolysis of LGA.…”
Section: Introductionmentioning
confidence: 99%